Information governance - García-Morales, Elisa (Anuario ThinkEPI, 2012)
Information governance is a term that is becoming increasingly important in relation to both professional and business spheres and in particular to market technology. Various conceptual approaches about its significance and its development are analyzed, concluding that it facilitates the positioning of information at a strategic level and responds to the need to establish rules and policies that allow the effective use of information inside an organization.
Keywords: Information governance; Information governance maturity model.